Resilience and diversity in children and families - Katz, I (My University, 2007)
Why do rich children have good outcomes, what makes some migrant children succeed in Australia and what does this tell us about resilience in populations? This presentation explores these areas using data from the Longitudinal Study of Australian Children.
Keywords: Families; Families and relationships; Families; Families and relationships